Challenges facing the farm animal veterinary profession in England: a qualitative study of veterinarians’ perceptions and responses - Ruston, Annmarie; Shortall, Orla; Green, Martin J.; Brennan, Marnie L.; Wapenaar, Wendela; Kaler, Jasmeet (Elsevier, 2016)
The farm animal veterinary profession in the UK has faced a number of challenges in recent decades related to the withdrawal of government funding and a contraction of the agricultural sector. They have come under pressure to respond by developing skills and focusing on disease prevention advisory services. However, this puts veterinarians in competition with other providers of these services, and moves in this direction have only been partial. Failure to respond to these challenges puts the veterinary profession at risk of de-professionalisation—a loss of their monopoly over knowledge, an erosion of client beliefs in their service ethos and a loss of work autonomy. This paper explores how farm animal veterinarians in England perceive these challenges and are responding to them.